Sumber Daya Manusia sebagai Aset Perusahaan: Studi Empiris Pengaruh Deskripsi Jabatan dan Spesifikasi Jabatan terhadap Efektivitas Kerja Karyawan - Santika, Ragana (Kajian Manajemen dan Bisnis, 2010)
The study was aimed at knowing how the influence of the implementation of job description and the work of the job specification on the work effectiveness as the company's asset. To collect the data, survey was used. The data were collected by asking respondents to fill the questionnaire. The respondents were chosen by using simple random sampling.